Digital Divide and the Use of Digital Public Services During the COVID-19 Pandemic - Slijepčević, Sunčana (Naše gospodarstvo/Our economy, 2023)
The COVID-19 pandemic enhanced digital transformation. With the spread of the pandemic and the introduction of epidemiological measures, citizens were enforced to use the Internet to an increased extent. The digital divide among citizens and the capability of citizens to get an equal level of services has also come to the fore. The paper explores the changes in the use of e-government services and the impact of the pandemic on the citizens’ attitudes toward Internet use in Croatia. The analysis is based on the survey data. The results show that due to the pandemic, citizens became more dependent on IT equipment. Citizens spend more time using digital public services than in the pre-pandemic period. The results also reveal differences in the COVID-19 impact on the use of digital public services between different groups of population.